Designing a Model for Knowledge Socialization Using Sociability Processes of Human Resource Management: A Case Study - Rezaei, K.; Babaei, M. (Engineering, Technology & Applied Science Research, 2017)
This study develops a model for knowledge socialization using sociability processes of human resources through an applied research approach. Two types of participants participated in this study. The first type included academic and industrial experts; the second type included employees and managers of Ansar Bank. Ten experts were asked to identify criteria and weigh the identified criteria. Using simple random sampling, the sample size was estimated at 207. Field and archival studies were used to collect data. Validity and reliability of the distributed questionnaire were confirmed by organizational experts. Using theoretical literature and surveying experts, 18 criteria were identified of which 12 criteria (desirable and joyful workplace, management and leadership support in sociability process, training courses, transparency in working relations, team work, organizational trustful climate, job description and job knowledge, tangible incentives, participatory system, informal technique, defined career path, individual values aligned with organizational value) were selected by screening for prioritization and analysis. Fuzzy AHP and structural equation modelling based on partial least squares were used for prioritization and weighting. Fuzzy AHP model showed that desirable workplace (0.163), participatory systems and brainstorming (0.149), transparency in working relations (0.114), and informal techniques (0.111) gained the highest weights; finally, PLS model showed that all 12 identified criteria were effective on socialization of knowledge management.